Snail-Eating Snails of Florida, Gastropoda - Kurt Auffenberg; Lionel Stange (EDIS)
This document provides an overview of the snail-eating snails found in Florida, detailing three native and two introduced species. It highlights the identification, distribution, and habits of these predatory snails, including the well-known rosy wolfsnail (Euglandina rosea) and the decollate snail (Rumina decollata). The document also discusses the ecological impact and biological control potential of these species, emphasizing their role in managing other snail populations. Published: November, 2001.